2016
DOI: 10.1016/j.brainresbull.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of blueberry extract on behavioral and biochemical dysfunctions in rats submitted to a model of manic behavior induced by ketamine

Abstract: The aim of the present study was to evaluate the protective effects of blueberry extract on oxidative stress and inflammatory parameters in a model of mania induced by ketamine administration in rats. Male rats were pretreated with blueberry extract (200mg/kg, once a day for 14days), lithium chloride (45mg/kg, mood stabilizer used as a positive control, twice a day for 14days), or vehicle. Between the 8th and 14th days, rats also received an injection of ketamine (25mg/kg) or vehicle. In the 15th day, thirty m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…In fact, the neurotoxic effects of kainic acid, in rats, have been reported to be reduced after consumption of blueberry, which ameliorated the exacerbated kainic acid induced inflammatory response in the hippocampus (Shukitt-Hale et al 2008). In fact, blueberry consumption (either directly or through anthocyanin rich extracts) has been demonstrated to have an in vitro neuroprotective effect against damage induced by an array of neurotoxic agents (such as trimethyltin and ketamine), while also exhibiting some in vivo effects in protecting and, in some cases, even enhancing the learning and memory capabilities of mice (Jo et al 2015;Andres-Lacueva et al 2005;Debom et al 2016). An effect that Krikorian et al (2010) showed to be expanded to humans, as the consumption of blueberries by older adults improved memory capabilities, which may be explained by an increase in synaptic plasticity resulting from a modulation of the microglia phenotype towards a more favorable M2 phenotype and an improvement of the microglia-neuron crosstalk through the increase of the expression of CX3CR1 receptor (an element of the CXCR1/CX3CL1 axis that connects microglia and neuron cells) (Meireles et al 2016).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…In fact, the neurotoxic effects of kainic acid, in rats, have been reported to be reduced after consumption of blueberry, which ameliorated the exacerbated kainic acid induced inflammatory response in the hippocampus (Shukitt-Hale et al 2008). In fact, blueberry consumption (either directly or through anthocyanin rich extracts) has been demonstrated to have an in vitro neuroprotective effect against damage induced by an array of neurotoxic agents (such as trimethyltin and ketamine), while also exhibiting some in vivo effects in protecting and, in some cases, even enhancing the learning and memory capabilities of mice (Jo et al 2015;Andres-Lacueva et al 2005;Debom et al 2016). An effect that Krikorian et al (2010) showed to be expanded to humans, as the consumption of blueberries by older adults improved memory capabilities, which may be explained by an increase in synaptic plasticity resulting from a modulation of the microglia phenotype towards a more favorable M2 phenotype and an improvement of the microglia-neuron crosstalk through the increase of the expression of CX3CR1 receptor (an element of the CXCR1/CX3CL1 axis that connects microglia and neuron cells) (Meireles et al 2016).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…In order to follow the principles of the Three Rs (replacement, reduction, and refinement) in relation to animal experimentation, this study did not evaluated the per se effect of lithium. Previous studies using the same animal model of mania showed that lithium per se did not induce changes in behavior and brain oxidative stress parameters (Debom et al., 2016).…”
Section: Methodsmentioning
confidence: 87%
“…Ketamine alters glutamatergic neurotransmission because it acts as a noncompetitive antagonist of N‐methyl‐D‐aspartate receptor, inducing changes in the rat brain similar to those described in BD patients (Ghedim et al., 2012). In addition, ketamine increases the locomotor activity in animals, and this effect of ketamine is attenuated by lithium treatment (Debom et al., 2016). Our findings showed that ketamine induces manic‐like behavior in rats that was evaluated using the open field test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations